SENSITIFITAS DAN SPESIFISITAS INSPEKSI VISUAL ASAM ASETAT PADA LESI SERVIKS DI DESA NYAMBU KEDIRI TABANAN - Mayun Mayura, I Gusti Putu (E-Journal Obstetric & Gynecology Udayana, 2015)
Introduction : Cervical cancer is the second commonest cancer that affectswomen through out the world.. Its clinical manifestation through molecular and cellular changes are metaplasia and dysplasia. Visual inspection of the cervix by acetic acid ( VIA ) is one of the many screening tools to aid the diagnosis of dysplasia which are caused by HPV infection.   Objective : To identify a positive visual inspection by acetic acid test withpositive human papilloma virus test in cervical lession and a positive visual inspection test with negative human papilloma virus test in cervical lession.   Subject and method : This research is across sectional study .One hundred andfifty samples were included in this study which were identified at the participating local community health center who agreed and are qualified. All samples were inspected and had the PAP Smear test thus the patient was examined by a qualified and trained personel to visual inspection by acetic acid. The result of the VIA test were then compared to the result of the PCR test which were then calculated with chi square and analysed by the t- independent test.   Result : The average age of the sample who are VIA positive is 37,67±5,66 andwith negative result is 34,96±8,19. Results from the t-independent test shows there is no statistical differences in the average age of the subjects (p>0,05). Analysis with the 2x2 table identified sensitivity of 72,73%; specificity 97,12%; negative prediction 97,83% positive prediction 66,67%; ratio of positive probability 25,27; ratio of negative probability 0,28% and an accuracy of 95,33%.   Conclusion: Based on the research result above we may conclude that this simpletest is spesific and sensitive in diagnosing dysplasia thus quiet reliable as a screening tool to detect cervical carcinoma in its early stages.   Key word : Cervical cancer, Visual inspection by acetic acid (VIA)